"Analysis of the Relationship Between the Mathematics Learning Process and the Daily Life Skills of Class I Min 2 Students in West Lombok" - Wardani, Eni Puspa; Wardani, Jani; Barokah, Titik (JUPE : Jurnal Pendidikan Mandala, 2024)
This research aims to analyze the relationship between the mathematics learning process and the daily life skills of class I MIN 2 West Lombok students. The method used in this research is qualitative with approach, observation, interviews and documentation. The subjects of this research consisted of the IC class and the homeroom teacher of MIN 2 West Lombok. Data collection was carried out through direct observation during the learning process, interviews with teachers to find out teaching methods and challenges faced, as well as interviews with students to find out their experiences in learning mathematics. From the results of documentation and field notes and the results of student work are also used to support the analysis. The research results show that the majority of students have difficulty understanding mathematics learning material. Connecting learning material to daily life skills can help students understand them. Additionally, using mathematics in real-world situations helps students understand the meaning of their learning, which can increase learning motivation.